An iron-based metal–organic framework as a novel dispersive solid-phase extraction sorbent for the efficient adsorption of tetrabromobisphenol A from environmental water samples. Issue 3 (3rd January 2023) - Wang, Ling-Juan; Han, Wei; Lou, Ting-Ting; Ma, Lin-Lin; Xiao, Ya-Bing; Xu, Zhou; Chen, Mao-Long; Cheng, Yun-Hui; Ding, Li
Abstract : A dispersive solid-phase extraction method based on Fe-MIL-88-NH2 combined with HPLC was developed for tetrabromobisphenol A in water samples. Abstract : For environmental safety, it is important to establish a simple, rapid, and sensitive method for emerging pollutants. Here, a dispersive solid-phase extraction (d-SPE) method based on an iron-based metal–organic framework (Fe-MIL-88-NH2 ) combined with high-performance liquid chromatography (HPLC) was developed for tetrabromobisphenol A (TBBPA) in water samples. Fe-MIL-88-NH2 was synthesized using a solvothermal method and completely characterized. Fe-MIL-88-NH2 had good water stability and gave a maximum adsorption capacity of 40.97 mg g −1 for TBBPA. The adsorption of TBBPA on Fe-MIL-88-NH2 followed Langmuir adsorption models and a pseudo-second-order kinetic model. The bromine ion and the hydroxyl group of TBBPA could form strong hydrogen bond interactions with the amino protons around the cavity of Fe-MIL-88-NH2, which was in accord with the molecular simulation calculations. Furthermore, several important d-SPE parameters were optimized, such as the amount of materials, extraction time, pH, ionic strength, elution solvent type, and volume. The established method showed good linearity in the concentration range of 0.005–100 μg g −1 ( r 2 ≥ 0.9996). This method's limits of detection (LOD) and quantification (LOQ) were 0.001 μg g −1 and 0.005 μg g −1, respectively. The recoveries in spiked water samples ranged from 87.5% to 104.9%. The proposed method was applied successfully to detect TBBPA in environmental water samples.